Pengaruh Kompetensi Guru Terhadap Prestasi Belajar Siswa Di MTs. Negeri 3 Kota Tasikmalaya - Rivan Marup; Caswita Caswita; Husni Mubarok (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Teacher competence refers to a set of essential abilities that teachers must possess to perform effectively, impacting student learning outcomes. This competence includes pedagogic, social, personality, and professional skills. This study aims to: (1) assess teacher competence's impact on student learning achievement at MTs.Negeri 3 Tasikmalaya City, (2) evaluate student learning achievement at MTs.Negeri 3 Tasikmalaya City, and (3) determine the extent of teacher competence's influence on student learning achievement at MTs.Negeri 3 Tasikmalaya City. The study framework is based on Wina Sanjaya's theory, examining student learning achievement in cognitive, affective, and psychomotor aspects. The research employs a quantitative survey method with descriptive and associative approaches, collecting data through documentation, questionnaires, interviews, and observations. Findings indicate a strong positive correlation between teacher competence (X) and student learning achievement (Y) at MTs.Negeri 3 Tasikmalaya City, with an r count of 0.979, surpassing the r table value of 0.316 at a 5% significance level. This confirms the hypothesis that teacher competence (X) significantly influences student learning achievement (Y). Moreover, the coefficient of determination is 95.8%, indicating that teacher competence accounts for 95.8% of the variance in student learning achievement, while 4.2% is attributable to unexamined variables.